Exploring the role of the Jumonji/ARID1 family of proteins during embryonic stem cell differentiation and X-chromosome inactivation - Matias, Neuza Maria Reis, 1987- (2011)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2010